Technical feasibility of visualizing myenteric plexus using confocal laser endomicroscopy. Issue 9 (September 2017) - Kobayashi, Masakuni; Sumiyama, Kazuki; Shimojima, Naoki; Ieiri, Satoshi; Okano, Hideyuki; Kamba, Shunsuke; Fujimura, Takumi; Hirobe, Seiichi; Kuroda, Tatsuo; Takahashi‐Fujigasaki, Junko
Abstract: Background and Aim: In preceding studies, we identified that the myenteric plexus (MP) could be visualized with confocal laser endomicroscopy (CLE) by applying neural fluorescent probes lacking clinical safety profiling data from the submucosal side. In this study, we evaluated the technical feasibility of MP visualization using probe‐based CLE (pCLE) from the serosal side with cresyl violet (CV), which has been used clinically for chromoendoscopy. Methods: The dye affinity of CV for MP was first explored in an in vivo transgenic mouse model using neural crest derivatives labeled with green fluorescent protein. We also tested the feasibility of CV‐assisted visualization of MP in human surgical specimens, wherein the tissue dying and pCLE observation were performed from the serosal side. In the human study, rate of MP visualization by pCLE was evaluated as the primary outcome. We also evaluated the sensitivity and specificity of MP visualization by pCLE, using pathological presence/absence of MP as the gold standard. Results: We confirmed the dye affinity of CV to MP in all tested models. The MP appeared as brightly stained ladder‐like structures with pCLE, and in the human study, MP was visualized in 12/14 (85.7%) samples, with 92.3% sensitivity and 100% specificity. In positive cases showing the ladder‐like structure of MP by pCLE, the mean maximum and minimum widths of nerve strands were 54.3 (± 23.6) and 19.7 (± 6.0) μm, respectively. A ganglion was detected by pCLE in 10 cases (10/12, 83.3%). Conclusions: This study demonstrated the technical feasibility of visualizing the MP in real time by CV‐assisted pCLE (UMIN‐CTR number, UMIN000015056).